2008
DOI: 10.4102/curationis.v31i2.981
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the relationship between the socio-economic and health status of the Coloured people of the Western Cape in an urban setting

Abstract: A descriptive non-experimental approach was applied to investigate and describe the prevalence of factors influencing the health status of the Coloured people of the Western Cape in an urban setting as a dissertation for a doctorate degree. For the purpose of this article the relationship between the socio-economic and health status of the Coloured people of the Western Cape in an urban setting are described. The study only included economically active persons < 21 ^ 50 years. The objective was to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“… 2008 ; Stellenberg et al . 2008 ). Nevertheless, it is suggested that: [ s ]trategies that narrowly focus on poverty and health without the broader perspectives offered by equity and human rights may fail because they do not take into consideration the key factors that often influence the relationship between poverty and ill-health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2008 ; Stellenberg et al . 2008 ). Nevertheless, it is suggested that: [ s ]trategies that narrowly focus on poverty and health without the broader perspectives offered by equity and human rights may fail because they do not take into consideration the key factors that often influence the relationship between poverty and ill-health.…”
Section: Discussionmentioning
confidence: 99%
“…They identified that chronic diseases such as asthma, smoking and abuse of alcohol were more prevalent amongst the poor than the rich; poorer areas are still plagued by a high burden of disease. To further substantiate this finding, Stellenberg, Welmann and Groenewald ( 2008 ) found a statistical relationship between the health status and the socioeconomic level of the coloured people of the Western Cape.…”
Section: Introductionmentioning
confidence: 91%
“…The most recent study investigating SEV in the African population was the South African Demographic and Health Survey (SADHS) in 2003 [9]. More recently, the relationship between SEV and health status in economically active subjects has been looked at by Stellenberg et al [16], in the coloured population and Malhotra [4], in the black African population in the Western Cape. Unfortunately there are very few studies that look at the SEV as predictors of health, especially in pregnant women in the black South African population [2, 17].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the study, 25.8% of inhabitants lived in informal settlements (Erasmus, Mans & Jacobs, 2006). Factors identified in the area that adversely influenced health included unemployment, low socio-economic levels and crime (Stellenberg et al, 2008). The social habits of this community revealed an inordinate amount of substance and alcohol abuse.…”
Section: Research-intensive University: a Project From The Universitymentioning
confidence: 99%